Rastin Crowdfunding (RCF): A Financial Subsystem of Rastin Banking - Bidabad, Bijan (International Journal of Islamic Banking and Finance Research, 2019)
Expansion and development of social networks have provided new backgrounds for financial activities. Based on Rastin Banking Regulations, crowdfunding can be installed to apply social networks in the direction of Islamic finance. Two methods of crowdfunding are introduced in Rastin Crowd Funding. Sponsor Crowd Funding (SCF) is for the absorption of peoples’ funds for special protective goals in the form of non-profit and free payments to an entrepreneur through banks. Peer to Peer Loan (PPL) is defined for absorption and collection of peoples’ funds for extending interest-free loans to a specific project of an entrepreneur.Regarding the characteristics of crowdfunding and application of social networks, the Crowd Funding System (CFS) is used as a web-based portal for absorption and collection of money resources for crowdfunding project through social networks in Rastin Banking.